2022
DOI: 10.1007/s12098-022-04370-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Umbilical Venous Catheter Insertion to Reduce Rate of Catheter Tip Malposition in Neonates: A Randomized, Controlled Trial: Authors’ Reply

Abstract: References1. Yadav A, Meena J, Kumar J. Ultrasound-guided umbilical venous catheter insertion to reduce rate of catheter tip malposition in neonates: a randomized, controlled trial: correspondence. Indian J Pediatr. 2022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Four of the six studies we identified illustrated a decrease in the occurrence of malpositioned or suboptimally positioned UVC tips when US was employed 1 3–5. This reduction ranged from 11.8% to 44.3%.…”
Section: Commentarymentioning
confidence: 96%
See 4 more Smart Citations
“…Four of the six studies we identified illustrated a decrease in the occurrence of malpositioned or suboptimally positioned UVC tips when US was employed 1 3–5. This reduction ranged from 11.8% to 44.3%.…”
Section: Commentarymentioning
confidence: 96%
“…Following screening of 62 titles and abstracts, 26 studies were reviewed in full, and 6 studies were included in this evidence review (table 1 and online supplemental table). 1–6…”
Section: Searchmentioning
confidence: 99%
See 3 more Smart Citations